PERENCANAAN ARSITEKTUR APLIKASI UNIVERSITAS LAMPUNG MENGGUNAKAN ZACHMAN FRAMEWORK - Ully Novianti S; Tristiyanto Tristiyanto (Universitas Lampung, 2017)
In the present era, to support business processes in a university requires the support of ICT in improving the quality of education and services. Analysis of the existing condition of ICT implementation in Unila using Zachman framework shows that the change in the need of application becomes the most dominant thing to be immediately corrected in various fields of work in dispersed work units. Application requirements analysis is obtained by interviewing, obervating, and giving questionnaires to internal and external customers, and conducting document study of strategic plan of Unila. The result of this research is planning of Unila application architecture in accordance with organizational purpose which can give input for management to prepare integrated application in the future.